2021
DOI: 10.1186/s43251-020-00025-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of time series prediction techniques for coastal bridge engineering

Abstract: In this study, three machine learning techniques, the XGBoost (Extreme Gradient Boosting), LSTM (Long Short-Term Memory Networks), and ARIMA (Autoregressive Integrated Moving Average Model), are utilized to deal with the time series prediction tasks for coastal bridge engineering. The performance of these techniques is comparatively demonstrated in three typical cases, the wave-load-on-deck under regular waves, structural displacement under combined wind and wave loads, and wave height variation along with typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Statistical models have achieved good prediction results when dealing with smooth sequences, but wind speed sequences are more volatile and have obvious nonlinear features, so it is difficult to accurately predict complex changes using only statistical models. The autoregressive integrated moving average (ARIMA) model [16] is a classic model for wind speed prediction, and Yu et al [17] utilized an ARIMA model to predict the bounded non-periodic data in coastal bridges. Unlike statistical methods, machine learning methods can better fit the nonlinear characteristics of wind speed and can recognize prediction patterns in the presence of relationship uncertainty in historical data [18].…”
Section: Related Workmentioning
confidence: 99%
“…Statistical models have achieved good prediction results when dealing with smooth sequences, but wind speed sequences are more volatile and have obvious nonlinear features, so it is difficult to accurately predict complex changes using only statistical models. The autoregressive integrated moving average (ARIMA) model [16] is a classic model for wind speed prediction, and Yu et al [17] utilized an ARIMA model to predict the bounded non-periodic data in coastal bridges. Unlike statistical methods, machine learning methods can better fit the nonlinear characteristics of wind speed and can recognize prediction patterns in the presence of relationship uncertainty in historical data [18].…”
Section: Related Workmentioning
confidence: 99%
“…SVR has been used in financial time series forecast and exchange rate forecasting [ 23 , 24 ]. GBM algorithm was applied to deal with the time series prediction tasks for coastal bridge engineering [ 25 ]. A random forest based regression model was developed in [ 26 ] to predict daily evapotranspiration from in-situ meteorological data and fluxes, satellite leaf area index (LAI), and land surface temperature data and found that the LAI is the most important feature.…”
Section: Introductionmentioning
confidence: 99%
“…A novel model was proposed based on Extreme Learning Machine (ELM) and laboratory experiments to estimate the tsunami wave forces on coastal bridges [33]. The effects of three different machine learning techniques in predicting the wave loads on bridge decks were also compared [34]. It is proved that machine learning techniques can provide guidance for time-history prediction requirements.…”
Section: Introductionmentioning
confidence: 99%